2016
DOI: 10.1016/j.cgh.2016.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Infliximab in Patients With Ulcerative Colitis Is Associated With Increased Risk of Relapse: A Multinational Retrospective Cohort Study

Abstract: In a multinational retrospective cohort study of patients with UC in sustained clinical remission, we associated discontinuation of infliximab with an increased risk of relapse. Treatment re-initiation is effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 17 publications
(14 reference statements)
2
37
0
Order By: Relevance
“…Drug discontinuation has been proposed but led to a high relapse rate. [4][5][6][7] Alternatively, treatment de-escalation by lowering the dose or increasing the interval between infusions allows decreasing drug exposure while maintaining efficacy. Recent data support the relevancy of de-escalation, as higher infliximab levels were reported to be linked to an increased risk of infections.…”
mentioning
confidence: 99%
“…Drug discontinuation has been proposed but led to a high relapse rate. [4][5][6][7] Alternatively, treatment de-escalation by lowering the dose or increasing the interval between infusions allows decreasing drug exposure while maintaining efficacy. Recent data support the relevancy of de-escalation, as higher infliximab levels were reported to be linked to an increased risk of infections.…”
mentioning
confidence: 99%
“…Infliximab is a medication used to treat patients with autoimmune and chronic inflammatory diseases . Notably, besides improving joint pain, swelling and inflammation, infliximab also reduces the levels of serum insulin, fasting glucose and insulin resistance in patients with ankylosing spondylitis and rheumatoid arthritis .…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab (Remicade ® ) is a chimeric monoclonal IgG1 antibody that specifically binds to TNF‐alpha and prevents the interaction of TNF‐alpha with TNF‐alpha receptor (TNFR) 1 and TNFR2 . For this reason, infliximab has been used to treat a variety of autoimmune and chronic inflammatory diseases such as rheumatoid arthritis, Crohn's disease, ulcerative colitis, psoriatic arthritis and ankylosing spondylitis . Interestingly, besides exerting anti‐inflammatory actions, infliximab has been also shown to improve insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from a recent retrospective study [39] indicated that 48 % of patients who maintained clinical remission for at least 12 months and then discontinued IFX had clinical relapses. The rate of relapse was significantly higher in patients who discontinued IFX (23.3 per 100 person-years) compared to patients who did not discontinue IFX (7.2 per 100 personyears).…”
Section: Anti-tnfa Treatmentmentioning
confidence: 99%